STRATEGI PEMASARAN RAMAH LINGKUNGAN PADA USAHA DAUR ULANG DI TANGERANG - Djakasaputra, Arifin; Valentina; Djaja, Tara Clarisa (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2023)
The purpose of this activity is to help business owners have knowledge about environmentally friendly marketing strategies. Given that the selected partners are engaged in the recycling business, they should be able to market products in accordance with the basic concept of partners in maintaining and preserving environmentally friendly marketing. This is very necessary in overcoming hazards to the environment, in addition to fulfilling human desires by minimizing the detrimental effects caused by the excessive use of natural resources. Partners utilize unused items, such as Aqua bottles, used cans, and others, which are then processed into products that have selling value. The partner location is in the Tangerang area. The method offered to partners is training/socialization delivered in the form of PowerPoint-based presentations (PPT). The training materials included an introduction to green marketing, production, use, and disposal processes, benefits and advantages of green marketing, and other related topics. The results of this activity show that the training runs smoothly and can optimize the ability of partners in terms of green marketing. Thus, the "handy craft" activities of the partners' recycled products can be sustained.